Minimally Invasive Modified Bentall Operation in a Young Chinese Male with Severe Aortic Regurgitation Secondary to Infective Endocarditis in the Background of Bicuspid Aortic Valve Having a Rudimentary Coronary Ostia: A Case Report - Sazzad, Md Faizus (2021)
Insights in Chest Diseases